An Exploratory Factor Analysis of the Location -Specific Antecedents to Foreign Direct Investment in Post- Crisis Zimbabwe (2009 - 2015) - Matiza, Tafadzwa; Perks, Sandra (Journal of Economics and Behavioral Studies, 2018)
While there are a plethora of studies based on the generic determinants of foreign direct investment, there is a discernible dearth of research into location - specific antecedents of distinct foreign direct investment typologies. This paper identifies the location- specific antecedents influencing foreign investors considering exploiting international business opportunities in post- crisis Zimbabwe. The literature provided the bases for the propositions advanced by this paper. Quantitative survey data was generated from a purposive sample of n=305 foreign investors. An exploratory factor analysis was conducted. The findings suggest that post- crisis Zimbabwe possesses the location- specific antecedents required by market- , resource - , efficiency-, and strategic asset- seeking FDI inflow. It is recommended that Zimbabwean policy- makers take cognisance of these nuances and implement appropriate market entry strategies to lure investors to Zimbabwe to grow the post- crisis economy.